Implementation in nutrition: A tools map - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
The Knowledge for Implementation and Impact Initiative (KI3) set out to strengthen the availability, access to, and utilization of implementation knowledge to accelerate progress in scaling up implementation and impact on nutrition. It was recognized that implementers need practical, curated, and hands-on implementation knowledge that is country specific and accounts for different social, political, and economic realities. In response to this need, KI3 systematically mapped the organizations and initiatives that already provide knowledge and tools on implementation for nutrition actions. The result was a database of entities that provide knowledge within the implementation science field. It includes 50 implementation knowledge providers, very few of which are physically based in low- and middle-income countries. To test the usefulness of the resources identified, we then piloted an approach to make them more accessible through the development of an online tools map. This pilot tools map could then provide the basis for interested parties to build upon if further funding could be made available.